NOTABLE MODIFICATIONS OF SUSHRUT SAMHITA BY DALHANA ON KSHARAPAKAVIDHI ADHAYAYA - M Borkar, Kanchan; V. Shekokar, Anantkumar (International Journal of Ayurveda and Pharma Research, 2015)
Ksharapakavidhi Adhyaya is one of the important chapters described in Sushrut Samhita sutrastana. Kshara (caustics) are superior and potential to achieve Chedana (excision), Bhedana (incision), Lekhana (scraping), because of their power to alleviate all the three Doshas. Acharya Vaghbhata and Sushruta advocated its importance in several diseases where surgery is difficult and futile. The commentary on Sushrut Samhita which is available in complete form is Nibhandha Sangraha by Dalhana. Acharaya Dalhana commented on Sushruta quotations gave further modifications on the quotations. Now a days the world recognizes the pioneering nature of Sushruta Kshara Karma Chikitsa and hence modern science also accepts Kshara as an alkali and uses it in various infected wounds. The present review describes the historical perspective of Kshara Karma as described in Ayurveda by Acharya Sushruta and Dalhana.